The kids are alright - labour market effects of unexpected parental hospitalisations in the Netherlands - Sara Rellstab; Pieter Bakx; Pilar Garcia-Gomez; Eddy van Doorslaer (Tinbergen Institute, 2018)
Unexpected negative health shocks may have serious consequences for labour force participation, not only for those who incur the shock but also for their family members. In particular, adult children may spend substantial time providing informal care and may incur stress-induced mental health problems following a parental health shock, which may in turn lead to reductions in labour supply. We link administrative data on labour market outcomes, hospitalisations and family relations for the full Dutch population for the years 1999-2008 to evaluate the effect of an unexpected parental hospitalisation on the probability of employment and on conditional earnings for the working age population. Using a difference-in-differences model combined with coarsened exact matching and individual fixed effects, we find no effect of an unexpected parental hospitalisation on either the probability of employment or conditional earnings for Dutch men and women, and neither for the full population nor for subpopulations most likely to become a caregiver. These findings suggest that the extensive public coverage of formal long-term care in the Netherlands provides sufficient opportunities to deal with adverse health events of family members without having to compromise one's labour supply.
Keywords: J22; J14; J10; I10; 330; Labour supply; parental health shocks; informal care